Serratia marcescens Infections in Neonatal Intensive Care Units (NICUs) - Cristina, Maria Luisa (Int J Environ Res Public Health, 2019)
Serratia marcescens belongs to the family Enterobacteriaceae, which is commonly found in water, soil, animals, insects, plants. Although S. marcescens displays relatively low virulence, it causes nosocomial infections and outbreaks in severely immunocompromised or critically ill patients, particularly in settings such as intensive care units (ICUs), especially neonatal units (NICUs). This microorganism gives rise to a wide range of clinical manifestations in newborns: from asymptomatic colonization to keratitis, conjunctivitis, urinary tract infections, pneumonia, surgical wound infections, sepsis, bloodstream infection and meningitis. The most frequent site of infection is the bloodstream, followed by the respiratory apparatus and the gastrointestinal tract. Strains of S. marcescens involved in epidemic events have frequently proved to be multi-resistant. Indeed, this species displays intrinsic resistance to several classes of antibiotics. Often, the specific source of the infection cannot be identified. However, the contaminated hands of healthcare workers are believed to be a major vehicle of its transmission. In neonatal intensive care units, colonized or infected newborns are the main potential source of S. marcescens, particularly in the respiratory apparatus, but also in the gastrointestinal tract. The early identification of colonized or infected patients and the prompt implementation of infection control measures, particularly rigorous hand hygiene and contact precautions, are essential in order to curb the spread of infection.